Multidisciplinary decision making in the management of hepatocellular carcinoma: A hospital-based study - Zaky, Saad; A. Makhlouf, Nahed; Abdel-Malek, Mohamed O; Bakheet, Ahmed A.; Seif, Hany M. A.; Hamza, Hesham M.; M. Sabry, Abeer M. (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To evaluate the short-term outcome of the decision taken by the Hepatoma Board for the treatment of Hepatocellular carcinoma (HCC). Materials and Methods: This was a prospective descriptive study involving 74 patients with HCC diagnosed by the known criteria. The decisions taken by the Hepatoma Board for the 74 patients were as follows: 1- surgical resection (7 patients), 2- local ablative therapy (LAT) (22 patients), 3- conventional transarterial chemoembolization (TACE) (24 patients), and 4- palliative supportive care (21 patients). Results: The short-term mortality rate was 25.7% of the total patients. The success rate was nearly equal in LAT (68.2%) and surgery (71.4%), whereas the success rate was approximately 33.3% in TACE. There was no difference in the mean total bilirubin level before and after LAT, surgery, or TACE (p>0.05 for each). There was a significant decrease in the mean serum albumin level after TACE (p=0.000). There was a decrease in the mean alpha fetoprotein level after surgery and LAT (p=0.033) for surgery and (p=0.048) for LAT. Conclusion: The management of HCC is better performed through a multidisciplinary team decision. Surgery has comparable outcome to LAT but is more invasive. According to our local experience, conventional TACE has a success rate of 33.3%.